Radical-Driven Methane Formation in Humans Evidenced by Exogenous Isotope-Labeled DMSO and Methionine - Frank Keppler; Mihály Boros; Daniela Polag (MDPI AG, 2023)
Methane (CH4), which is produced endogenously in animals and plants, was recently suggested to play a role in cellular physiology, potentially influencing the signaling pathways and regulatory mechanisms involved in nitrosative and oxidative stress responses. In addition, it was proposed that the supplementation of CH4 to organisms may be beneficial for the treatment of several diseases, including ischemia, reperfusion injury, and inflammation. However, it is still unclear whether and how CH4 is produced in mammalian cells without the help of microorganisms, and how CH4 might be involved in physiological processes in humans. In this study, we produced the first evidence of the principle that CH4 is formed non-microbially in the human body by applying isotopically labeled methylated sulfur compounds, such as dimethyl sulfoxide (DMSO) and methionine, as carbon precursors to confirm cellular CH4 formation. A volunteer applied isotopically labeled (2H and 13C) DMSO on the skin, orally, and to blood samples. The monitoring of stable isotope values of CH4 convincingly showed the conversion of the methyl groups, as isotopically labeled CH4 was formed during all experiments. Based on these results, we considered several hypotheses about endogenously formed CH4 in humans, including physiological aspects and stress responses involving reactive oxygen species (ROS). While further and broader validation studies are needed, the results may unambiguously serve as a proof of concept for the endogenous formation of CH4 in humans via a radical-driven process. Furthermore, these results might encourage follow-up studies to decipher the potential physiological role of CH4 and its bioactivity in humans in more detail. Of particular importance is the potential to monitor CH4 as an oxidative stress biomarker if the observed large variability of CH4 in breath air is an indicator of physiological stress responses and immune reactions. Finally, the potential role of DMSO as a radical scavenger to counteract oxidative stress caused by ROS might be considered in the health sciences. DMSO has already been investigated for many years, but its potential positive role in medical use remains highly uncertain.